Użądlenia owadów błonkoskrzydłych w gałkę oczną – objawy kliniczne, ich patomechanizm i leczenie - Cichocka-Jarosz, Ewa; Węglarz, Monika; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Eyeball is a rare stings location additionally with very special immunology response, with no systemic anaphylactic reactions. The ACAID (Anterior Chamber Associated Immune Deviation) phenomenon causes a special immunology privilege of the eyeball, which prevents late immunological answer reaction and destruction processes of the anterior part of the eye. In case that sting penetrates the eyeball local allergic reaction can appear despite ACAID phenomenon. Adequate treatment is necessary for those patients. It can lead to permanent visual acuity deterioration.